Lithium cobalt oxide positive electrode material prepared based on stoichiometric ratio and method thereof
By regulating the lithium content and using stoichiometric ratio to prepare lithium cobalt oxide positive electrode material, ensuring that only Co3+ is contained in the material, solving the problem of decreasing battery life caused by Co2+, and significantly improving the circulation performance and volume energy density.
Patent Information
- Application Number
- CN202411664845.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-25
AI Technical Summary
In the process of increasing the LiCoO2 charging cutoff voltage to obtain a higher volume energy density, the Co2+ generated in the battery material will cause a decrease in the battery life, and it is easy to destroy the SEI film and deposit it on the negative electrode surface during the charging and discharging process, causing a vicious cycle and reducing battery performance.
By regulating the lithium content and using stoichiometric ratio to prepare lithium cobalt oxide positive electrode material, ensuring that only Co3+ is contained in the synthetic material to avoid the generation of Co2+. The method includes steps such as ingredients, sintering and secondary sintering. By heating up and cooling, the lithium content is controlled to ensure the stability of the material.
The lithium cobalt oxide material prepared by regulating the lithium content can significantly improve circulation performance, extend battery life, and increase volume energy density, solving the problem of battery performance degradation caused by Co2+.
Smart Images

Figure CN119683697A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium-ion battery positive electrode materials, and specifically to lithium cobalt oxide positive electrode materials and preparation methods thereof. Background Art
[0002] In order to meet the demand for higher energy density of rapidly updated consumer electronic products, increasing the cutoff voltage of LiCoO2 can achieve higher specific capacity and volume energy density.
[0003] However, while increasing the charge cut-off voltage brings higher volume energy density, it also brings some serious problems to battery materials that cannot be ignored, resulting in a sharp decrease in battery life. During material synthesis, since the lithium source is easily lost, we usually put in a slightly excessive amount of lithium source in the lithium-cobalt feed ratio. However, the excessive lithium source will cause the synthesized lithium cobalt oxide material to have Co 2+ , and Co 2+ During the charge and discharge process, it is easy to leave the surface of lithium cobalt oxide, enter the electrolyte, migrate to the negative electrode, destroy the SEI film and finally deposit on the negative electrode surface. This degradation starts from the surface structure, and the unstable surface structure will trigger more violent interface side reactions, forming a vicious cycle, leading to further decline in battery performance. Therefore, it is necessary to eliminate the Co generated during the synthesis of lithium cobalt oxide materials. 2+ It is very necessary to improve the performance of lithium cobalt oxide batteries. Summary of the invention
[0004] In view of the above problems, the present invention provides a method for preparing a high-voltage lithium cobalt oxide positive electrode material by regulating the lithium content.
[0005] In a first aspect, the present invention provides a method for preparing a lithium cobalt oxide positive electrode material based on a stoichiometric ratio, comprising the following steps:
[0006] (1) According to the lithium cobalt oxide positive electrode material Li 1-xy CoM y x+ O2, M are doping elements, and the ingredients are prepared, wherein the raw materials are ball-milled and mixed to obtain a mixed material;
[0007] (2) sintering the mixed material obtained in step 1 in an air atmosphere by programmed temperature increase and then cooling naturally;
[0008] (3) The material obtained in step 2 is ball-milled again, and a secondary sintering is performed in an air atmosphere by programmed temperature increase. The temperature is programmed to decrease to a specified temperature and then naturally decreased in temperature. The obtained material is ball-milled to obtain a lithium cobalt oxide positive electrode material.
[0009] Better, Li 1-xy CoM yx+ In O2, M is any one of the common doping elements such as Mg, Al, Cr, Ni, Ca, Ti, etc.
[0010] Better, Li 1-xy CoM y x+ In O2, y=0.001~0.05.
[0011] Preferably, in step (2), the sintering is performed once in an air atmosphere by using programmed temperature increase, which means: heating from room temperature to 900° C. for 12 hours in an air atmosphere for sintering once, and the heating rate is 10° C. / min.
[0012] Preferably, in step (3), programmed temperature is adopted to carry out secondary sintering in air atmosphere, and programmed temperature reduction to a specified temperature and then natural temperature reduction means: in air atmosphere, heating from room temperature to 1000°C and keeping the temperature constant for 12 hours for secondary sintering, the heating rate is 10°C / min, after the constant temperature is ended, the temperature is programmed to be reduced to 200°C and then naturally cooled to room temperature, the cooling rate is 2°C / min.
[0013] In a second aspect, the present invention provides a lithium cobalt oxide positive electrode material prepared by the method described in the first aspect.
[0014] In a third aspect, the present invention provides a use of a lithium cobalt oxide positive electrode material prepared by the method described in the first aspect.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] 1. The present invention is based on Li 1-xy CoM y x+ O2 is prepared in a stoichiometric ratio, and less lithium source is used. Only a simple solid phase reaction is required. The method is simple, the requirements for experimental equipment are low, and it has obvious economic benefits.
[0017] 2. The present invention uses the original lithium feed ratio during material synthesis to adjust the original lithium feed ratio so that the synthesized lithium cobalt oxide material contains only Co 3+ , providing an effective solution for material modification. Compared with the lithium cobalt oxide material made by adjusting the lithium content and the lithium cobalt oxide material made by not adjusting the lithium content, its cycle performance is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The X-ray diffraction diagrams of the lithium cobalt oxide positive electrode materials prepared in Examples 1 to 3 and Comparative Example 1 of the present invention.
[0019] Figure 2 The scanning electron microscope images of the lithium cobalt oxide positive electrode materials prepared in Examples 1 to 3 of the present invention and Comparative Example 1 are shown.
[0020] Figure 3 The following is a comparison chart of the 0.5C long cycle performance of button-type half-cells made from the lithium cobalt oxide prepared in Examples 1 to 3 and the lithium cobalt oxide prepared in Comparative Example 1 at 3 to 4.6V. DETAILED DESCRIPTION
[0021] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the essence of the present invention, modifications and substitutions made to the methods, steps or conditions of the present invention all belong to the scope of the present invention.
[0022] Embodiment 1
[0023] A method for preparing lithium cobalt oxide by regulating the original feed ratio of lithium source, wherein the lithium cobalt oxide is Li 0.95 CoMg 0.025 O2, comprising the following steps:
[0024] 1. At room temperature, according to Li 0.95 CoMg 0.025 O2 ingredients, a certain proportion of lithium carbonate, cobalt tetroxide and magnesium oxide are mixed, and the mixture is evenly mixed with a ball mill to obtain a mixed material; wherein the molar ratio of the cobalt element in the cobalt tetroxide to the magnesium element in the magnesium oxide is n(Co):n(Mg)=1:0.025, in order to keep the cobalt valence state at +3, the molar ratio of the lithium element in the lithium cobaltate to the cobalt element in the cobalt tetroxide should be n(Li):n(Co)=0.95:1 at this time; the ball mill speed is 500rpm, reversed every five minutes, and the total ball milling time is 30 minutes.
[0025] 2. Place the mixed material in step 1 in a muffle furnace for primary sintering. The specific process of the primary sintering is as follows: in an air atmosphere, heat the mixed material from room temperature to 900°C for 12 hours at a heating rate of 10°C / min. After the constant temperature is completed, naturally cool it to room temperature with the muffle furnace to obtain a block of primary sintered material; the primary sintered material obtained above is ball-milled in a ball mill at a ball milling rate of 500rpm, reversed every five minutes, and the total ball milling time is 10 minutes to obtain a primary crushed material.
[0026] 3. The primary crushed material in step 2 is placed in a muffle furnace for secondary sintering. The specific process of the secondary sintering is as follows: in an air atmosphere, the mixed material is heated from room temperature to 1000°C for 12 hours at a heating rate of 10°C / min. After the constant temperature is reached, the mixture is cooled to 200°C at a cooling rate of 2°C / min. After the programmed cooling is completed, the mixture is naturally cooled to room temperature in the muffle furnace to obtain a block of secondary sintered material; the secondary sintered material obtained above is ball-milled in a ball mill at a ball milling rate of 500rpm, and the mixture is reversed every five minutes. The total ball milling time is 10 minutes to obtain a secondary crushed material, which is then sieved.
[0027] Figure 1 The X-ray diffraction (XRD) diagram of the material prepared in Example 1 is shown. Figure 1 It can be seen that the material prepared in Example 1 corresponds well to the standard card of lithium cobalt oxide.
[0028] Figure 2 The scanning electron microscope (SEM) image of the material prepared in Example 1 is shown. Figure 2 It can be seen that the material prepared in Example 1 is a typical lithium cobalt oxide layered material.
[0029] The lithium cobalt oxide positive electrode material prepared in Example 1, the conductive agent Super-P, and the binder PVDF are mixed in a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone is added and ground for 20 minutes to obtain an electrode slurry. The electrode slurry is evenly coated on an aluminum foil and vacuum dried for 12 hours to obtain an electrode sheet. The prepared electrode sheet is used as the positive electrode, the lithium sheet as the negative electrode, celegard2500 as the diaphragm, 1M LiPF6 dissolved in an electrolyte solution of a mixture of EC and DEC in a volume ratio of 3:7, and 1wt% FEC additive as the electrolyte, and assembled into a CR-2032 button battery. The lithium cobalt oxide lithium-ion battery is subjected to a voltage of 3-4.6V and a charge of 0.5C (1C=274mAg -1 ) was used to test the cycle performance. Figure 3 shown.
[0030] Depend on Figure 3 It can be seen that the lithium cobalt oxide positive electrode material prepared in this embodiment shows excellent cycle performance, and the maximum discharge capacity is 204.6 mAh g at a current density of 0.5C. -1 , and after 300 cycles, 81% of the capacity is still retained, which has good cycle performance.
[0031] Embodiment 2
[0032] The lithium cobalt oxide prepared in this embodiment 2 is Li 0.9 CoMg 0.025O2, the difference from Example 1 is that in step 1, n(Li):n(Co)=0.9:1. The other steps and parameters are the same as those in Example 1.
[0033] Figure 1 The X-ray diffraction (XRD) diagram of the material prepared in Example 2 is shown. Figure 1 It can be seen that the material prepared in Example 2 corresponds well to the standard card of lithium cobalt oxide.
[0034] Figure 2 The scanning electron microscope (SEM) image of the material prepared in Example 2 is shown. Figure 2 It can be seen that the material prepared in Example 2 is a typical lithium cobalt oxide layered material.
[0035] The lithium cobalt oxide positive electrode material, conductive agent Super-P, and binder PVDF prepared in Example 2 are mixed in a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone is added and ground for 20 minutes to obtain an electrode slurry. The electrode slurry is evenly coated on an aluminum foil and vacuum dried for 12 hours to obtain an electrode sheet. The prepared electrode sheet is used as the positive electrode, the lithium sheet as the negative electrode, celegard2500 as the diaphragm, 1M LiPF6 dissolved in an electrolyte solution of a mixture of EC and DEC in a volume ratio of 3:7, and 1wt% FEC additive as the electrolyte to assemble into a CR-2032 button cell. The lithium cobalt oxide lithium-ion battery is subjected to a voltage of 3–4.6V and a charge of 0.5C (1C=274mAg -1 ) was used to test the cycle performance. Figure 3 shown.
[0036] Depend on Figure 3 It can be seen that due to the low lithium content, the maximum discharge capacity of the lithium cobalt oxide positive electrode material prepared in Example 2 at a current density of 0.5C is 191 mAh g -1 , which is quite different from the positive electrode material prepared in Example 1.
[0037] Embodiment 3
[0038] The lithium cobalt oxide prepared in this embodiment 3 is Li 1.1 CoMg 0.025 O2, the difference from Example 1 is that in step 1, n(Li):n(Co)=1.1:1. The other steps and parameters are the same as those in Example 1.
[0039] Figure 1 The X-ray diffraction (XRD) diagram of the material prepared in Example 3 is shown. Figure 1 It can be seen that the material prepared in Example 3 corresponds well to the standard card of lithium cobalt oxide.
[0040] Figure 2 The scanning electron microscope (SEM) image of the material prepared in Example 3 is shown. Figure 2 It can be seen that the material prepared in Example 3 is a typical lithium cobalt oxide layered material.
[0041] The lithium cobalt oxide positive electrode material, conductive agent Super-P, and binder PVDF prepared in Example 3 are mixed in a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone is added and ground for 20 minutes to obtain an electrode slurry. The electrode slurry is evenly coated on an aluminum foil and vacuum dried for 12 hours to obtain an electrode sheet. The prepared electrode sheet is used as the positive electrode, the lithium sheet as the negative electrode, celegard2500 as the diaphragm, 1M LiPF6 dissolved in an electrolyte solution of a mixture of EC and DEC in a volume ratio of 3:7, and 1wt% FEC additive as the electrolyte to assemble into a CR-2032 button cell. The lithium cobalt oxide lithium-ion battery is subjected to a voltage of 3–4.6V and a charge of 0.5C (1C=274mAg -1 ) was used to test the cycle performance. Figure 3 shown.
[0042] Depend on Figure 3 It can be seen that due to the excessive lithium content, the lithium cobalt oxide positive electrode material prepared in Example 3 has very poor long-cycle stability at a current density of 0.5C. After 300 cycles, only 48% of its capacity is retained, which is significantly different from the positive electrode material prepared in Example 1.
[0043] Comparative Example 1
[0044] The lithium cobalt oxide prepared in this comparative example is LiCoMg 0.025 O2, the difference from Example 1 is that in step 1, n(Li):n(Co)=1:1. The other steps and parameters are the same as those in Example 1.
[0045] Figure 1 The X-ray diffraction (XRD) pattern of the material prepared in Comparative Example 1 is shown. Figure 1 It can be seen that the material prepared in Control Example 1 corresponds well to the standard card of lithium cobalt oxide.
[0046] Figure 2 The scanning electron microscope (SEM) image of the material prepared in the comparative example 1 is shown. Figure 2 It can be seen that the material prepared in Control Example 1 presents a typical lithium cobalt oxide layered material.
[0047] The lithium cobalt oxide positive electrode material prepared in control example 1, the conductive agent Super-P, and the binder PVDF were mixed in a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone was added and ground for 20 minutes to obtain an electrode slurry. The electrode slurry was evenly coated on an aluminum foil and vacuum dried for 12 hours to obtain an electrode sheet. The prepared electrode sheet was used as the positive electrode, the lithium sheet as the negative electrode, celegard2500 as the separator, 1M LiPF6 dissolved in an electrolyte solution of a mixture of EC and DEC in a volume ratio of 3:7, and 1wt% FEC additive as the electrolyte to assemble a CR-2032 button battery. The lithium cobalt oxide lithium-ion battery was subjected to a voltage of 3–4.6V and a charge of 0.5C (1C=274mAg -1 ) was used to test the cycle performance. Figure 3 shown.
[0048] Depend on Figure 3 It can be seen that the maximum discharge capacity of the lithium cobalt oxide positive electrode material prepared in this comparative example 1 is 206 mAh g at a current density of 0.5C. -1 However, only 43% of its capacity is retained after 300 cycles, which is quite different from the positive electrode material prepared in Example 1.
Claims
1. A method for preparing a lithium cobalt oxide positive electrode material based on a stoichiometric ratio, characterized in that: The steps include: (1) According to the lithium cobalt oxide positive electrode material Li 1-xy CoM y x+ O2, M are doping elements, and the ingredients are prepared, wherein the raw materials are ball-milled and mixed to obtain a mixed material; (2) sintering the mixed material obtained in step 1 in an air atmosphere by programmed heating and then cooling naturally; (3) The material obtained in step 2 is ball-milled again, and a secondary sintering is performed in an air atmosphere by programmed temperature increase. The temperature is programmed to decrease to a specified temperature and then naturally cooled. The obtained material is ball-milled to obtain a lithium cobalt oxide positive electrode material.
2. The method according to claim 1, characterized in that Li 1-xy CoM y x+ In O2, M is any one of the doping elements Mg, Al, Cr, Ni, Ca, and Ti.
3. The method according to claim 1, characterized in that Li 1-xy CoM y x+ In O2, y = 0.001 to 0.
05.
4. The method according to claim 1, characterized in that In step (2), the sintering is performed once in an air atmosphere by using programmed temperature increase, which means that the sintering is performed once in an air atmosphere by heating from room temperature to 900° C. and maintaining the temperature for 12 hours, with a heating rate of 10° C. / min.
5. The method according to claim 1, characterized in that In step (3), programmed temperature is adopted to carry out secondary sintering in air atmosphere, and programmed temperature is lowered to a specified temperature and then naturally lowered to a specified temperature, which means: in air atmosphere, heating is carried out from room temperature to 1000°C and kept at a constant temperature for 12 hours for secondary sintering, and the heating rate is 10°C / min. After the constant temperature is ended, the temperature is lowered to 200°C and then naturally cooled to room temperature, and the cooling rate is 2°C / min.
6. A lithium cobalt oxide positive electrode material prepared by the method according to any one of claims 1 to 5.
7. Use of a lithium cobalt oxide positive electrode material prepared by the method according to any one of claims 1 to 5.